COMPETITIVENESS AND IT’S INFLUENCE IN THE TRADE BALANCE A STUDY FOR THE WESTERN BALKAN - Llatja, Adela (European Scientific Journal, ESJ, 2015)
European Membership is an important milestone for the countries of the Western Balkan. In order to become ready for the Internal Market the economies of the Western Balkan need to become competitive. Improving the trade balance has always been a challenge for the countries of the Western Balkan, but the right tools to influence it, are missing. Becoming more competitive will help the countries of the Western Balkan region improve their trade balance and also adopt better the obligations for EU membership. With a correlation analyses we will show that the trade balance can be improved by improving the goods markets efficiency, by making the business more sophisticated, and by improving the investment climate.